Milker′s nodule - Kaviarasan P; Yamini M; Prasad PVS; Viswanathan P (Indian Journal of Dermatology, 2009)
Milker′s nodule virus is a parapox virus that is endemic in cattle. The virus can be grown in tissue culture of both bovine and human cell lines. We report a 53-year-old male, milker who presented with multiple painful nodules on both hands for one month. The nodules were tender and showed central umblication and surrounding rim of erythema. Both epitrochlear and axillary lymph nodes were enlarged on both sides and were non-tender. The skin biopsy revealed marked edema in the epidermis with monouclear inflammatory cell infilitration in the upper dermis. The diagnosis was made on clinical basis. As there was no specific treatment the patient was managed only with antibiotics for secondary infection. The lesions partially resolved after two weeks. This case in reported for its occupational importance.